Utilizing Telegram And Whatsapp As Effective Substitute Media For Teaching English - Sandi Pradana (Journal on Education, 2022)
The study aims to analyze the effectiveness of Telegram and WhatsApp in teaching English as a second language based on the insights gathered from the interviews and data obtained from various sources. The method used in this study is the qualitative descriptive method. The qualitative descriptive method allows for a detailed exploration of the participants’ experiences and perceptions, which is crucial in understanding their preferences and attitudes toward these communication platforms. The data used in this study was obtained through interviews with 2 English lecturers and 20 students who learned English through Telegram and WhatsApp. Data is also taken from books, journals, and the internet. Both of these applications can be an effective alternative to learning English compared to Zoom, especially in the current post-pandemic that limits face-to-face teaching and learning activities. The advantages and disadvantages of each application must be considered and matched to the needs and preferences of each individual before deciding to use a particular application as an English learning medium.